Levantamento, identificação e mapeamento de estudos sobre nascentes localizadas no bioma caatinga: uma revisão sistemática de literatura - Failla, Sara Carvalho (2022)
The water crisis has grown into a chronic global problem, and the majority of the world's water-related ecosystems are suffering from pollution and degradation. The Caatinga biome is located in the Brazilian semi-arid region, which among the existing semi-arid regions is the most biodiverse and populous in the world. However, it has been one of the most threatened biomes in that country due to the various unsustainable human practices in the region. Therefore, the need for actions and studies dedicated to this ecosystem, which presents little scientific research, is notorious, especially regarding water courses and their sources, which, in addition to being scarce, are vulnerable to human activities and climate change. Mapping studies in the region dedicated to water issues and their recovery, are of paramount importance to stimulate well-timed and targeted actions aimed at reducing, reversing and avoiding environmental degradation, increasing food and water security. Given the above, the present study aimed to carry out a systematic literature review to map the springs located in the Caatinga biome and identify the impacts caused by human actions on their degradation. A literature review was conducted with research carried out on springs in the Caatinga. Searches were carried out using the main available databases, and the data found were mapped in order to highlight regions of low knowledge production. Initially, 1830 scientific papers were found with the search strings utilized, however, not a single scientific paper met all the established inclusion criteria and only 10 papers have partially met the selection criteria. The period of selected researches was from 2006 to 2021 and only five of the nine states that make up this biome have researches on this subject. It should be noted that the very low production made it impossible to carry out a more cohesive and complete systematic literature mapping, evidencing the great scarcity of studies and the importance of new scientific productions on this biome that is so important for the country.